1985
DOI: 10.1021/bi00328a021
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of interaction of 2-amino-6-mercapto-9-.beta.-ribofuranosylpurine 5'-triphosphate with bovine brain tubulin

Abstract: The binding of the guanine nucleotide analogue 2-amino-6-mercapto-9-beta-ribofuranosylpurine 5'-triphosphate (S6-GTP) to tubulin from which the associated proteins and exchangeably bound nucleotide have been removed produces about a 15% decrease in intrinsic tubulin fluorescence. Using a fluorescence stopped-flow technique, we have examined the kinetics and mechanism of this process. Analysis of the data reveals that the binding is complex, involving at least one conformational change subsequent to nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(72 reference statements)
5
5
0
Order By: Relevance
“…We studied the interference of pCopN with tubulin nucleotide exchange by recording the quenching of the fluorescence of tubulin's tryptophan residues upon substitution of GDP by S6-GDP (20,21). Fitting the data with a monoexponential decay function, we found a rate constant of 0.15 Ϯ 0.02 s Ϫ1 for tubulin alone, in agreement with previous results (21).…”
Section: Pcopn Sequesters Tubulin In a 1:1 Complex And Delayssupporting
confidence: 87%
“…We studied the interference of pCopN with tubulin nucleotide exchange by recording the quenching of the fluorescence of tubulin's tryptophan residues upon substitution of GDP by S6-GDP (20,21). Fitting the data with a monoexponential decay function, we found a rate constant of 0.15 Ϯ 0.02 s Ϫ1 for tubulin alone, in agreement with previous results (21).…”
Section: Pcopn Sequesters Tubulin In a 1:1 Complex And Delayssupporting
confidence: 87%
“…The rate of GTP dissociation from the 1:1 GTP-tubulin complex by excess S6-GTP was found to be 10-fold slower (0.012 s -1 ) under the same solution conditions. The dependence of the rate of dissociation of GDP on solution variables showed that glycerol (4 M) caused a 10fold decrease in the rate of GDP dissociation, in qualitative agreement with Yarbrough and Fishback (27). The rate of GDP dissociation increased (k ) 0.3 s -1 ) when the concentration of magnesium ions in P buffer was increased to 5 mM.…”
Section: Methodssupporting
confidence: 79%
“…Kinetics of GDP and GTP Dissociation from Tubulin in the Absence and Presence of Stathmin. The fluorescence decrease associated with the fluorescence resonance energy transfer from tryptophans to S6-GDP ( , ) was used to monitor the kinetics of S6-GDP exchange for tubulin-bound GDP and to examine how the kinetics were affected by the binding of stathmin to tubulin. GDP-tubulin 1:1 complex was first prepared by resuspending the pellet of precycled microtubules in ice-cold M buffer supplemented with 20 μM GDP.…”
Section: Methodsmentioning
confidence: 99%
“…4B). A prior measurement of GTP binding to yeast αβ-tubulin showed higher affinity (~50 nM; (Davis et al, 1993)); this discrepancy may be explained by the glycerol-free conditions we used (glycerol has been observed to increase the nucleotide binding affinity of αβ-tubulin (Yarbrough and Fishback, 1985)). Whatever the reason, our measurements showed that the β:C12A mutation caused a decrease in the affinity of GTP/GDP binding.…”
Section: Resultsmentioning
confidence: 84%